Bibliometric Mapping of Character Values Education in Schools - Hafid, Abdul; Sudarmin, Sudarmin; Salmia, Salmia (Journal of Innovation in Educational and Cultural Research, 2025)
This research is motivated by the critical need for an in-depth understanding of research trends concerning character education values within a global context, specifically those indexed in Scopus. The objective is to map and analyze these research trends from 2013 to 2023. The methodology employed is a bibliometric review, with data extracted from Scopus in November 2022 using the keyword "character education values in schools," subsequently analyzed descriptively and through network visualization using VOSViewer. The findings reveal a consistent annual increase in publications, with Universitas Sebelas Maret emerging as the most significant contributor from Indonesia, and the United States as the most productive country of foreign researchers. The most prolific Indonesian researcher is Arifin, and international collaborations predominantly occur with researchers from the United States and the United Kingdom. The dominant research subject is Character Education, with the research development map divided into 7 clusters. The study concludes that the field of character education values continues to evolve, presenting extensive research opportunities. This research contributes to the body of knowledge by providing a comprehensive overview of the trends and directions in character education values research globally, serving as a reference for future researchers in advancing this field.